Intergenerational Perspectives on Climate Resilience in Kenya: Systematic Review - Gichimu, Elizabeth Wangari; Menecha, Jared Bravin (Daystar University, School of Communication, 2025)
The purpose of this study will be to systematically review existing literature on intergenerational perspectives of climate resilience in Kenya, with the aim of identifying how different age groups perceive, experience, and respond to climate change-related challenges. Systematic review will be employed to collect, evaluate, and synthesize existing literature on intergenerational perspectives of climate resilience in Kenya. A comprehensive literature search will be conducted across academic databases between 2005 and 2025. Standardized data extraction forms will be used. Double extraction will be conducted to ensure accuracy and minimize bias. Qualitative data will be extracted and analyzed thematically to identify patterns in attitudes, coping strategies, and resilience frameworks across different age groups. It is anticipated that the review will reveal distinct intergenerational differences in perceptions, attitudes, and coping mechanisms related to climate resilience in Kenya. This will be important in designing all-inclusive and effective climate adaptation strategies that address different dimensions of resilience.
Conference Paper
Keywords: and synthesize existing literature on intergenerational perspectives of climate resilience in Kenya. A comprehensive literature search will be conducted across academic databases between 2005 and 2025. Standardized data extraction forms will be used. Double extraction will be conducted to ensure accuracy and minimize bias. Qualitative data will be extracted and analyzed thematically to identify patterns in attitudes; Climate Resilience; Intergenerational Perspectives